A study on the effects of pavement towards the surrounding thermal environment: A case study of Dataran Rakyat and Dataran Wawasan, Putrajaya - Abu Bakar, Aniza; Hj Mohd Ariffin, Noor Aziah; Azim, Ahmad Kamal; Ahmad, Zafirah (2013)
Rapid urbanization has turned most of the soil ground into paved surfaces whether it is building or outdoor landscape elements that make up majority of urban fabrics composition. Paved surfaces are one of the crucial elements that significantly influence the occurrence of urban heat island (UHI) phenomenon. All these surface paving elements vary in term of their ability to influence the arising of the surrounding temperature. It depends on the color, albedo, material, texture and so forth that demonstrated their capacity for storing, radiating, or emitting the heat from solar radiation. This research attempts in investigating the surface temperature of the diverse paving materials at two urban plazas which are Dataran Wawasan (exposed plaza) and Dataran Rakyat (partially shaded plaza) with some constant values such as same orientation, common resemblance of physical site context and dimension. As a result, this study shows the influences and significance of certain types of pavement surfaces that vary in term of its material, color, and texture towards the surrounding thermal environment of the studied sites and subsequently provide few recommendations through design initiatives that are feasible to mitigate the UHI effects in that particular areas. Keywords : Urbanization, urban heat island, pavement, thermal environment, glare